Public violence in Islamic societies : power, discipline, and the construction of the public sphere, 7th-19th centuries C.E. - Lange, Christian, 1975-; Fierro, Ma. Isabel (María Isabel) (Edinburgh University Press, 2009)
This exploration of the role of violence in the history of Islamic societies considers the subject particularly in the context of its implementation as a political strategy to claim power over the public sphere. Violence, both among Muslims and between Muslims and non-Muslims, has been the object of research in the past, as in the case of jihad, martyrdom, rebellion or criminal law. This book goes beyond these concerns in addressing, in a comprehensive and cross-disciplinary fashion, how violence has functioned as a basic principle of Islamic social and political organization in a variety of historical and geographical contexts. Contributions trace the use of violence by governments in the history of Islam, shed light on legal views of violence, and discuss artistic and religious responses. Authors lay out a spectrum of attitudes rather than trying to define an Islamic doctrine of violence. Bringing together some of the most substantive and innovative scholarship on this important topic to date, this volume contributes to the growing interest, both scholarly and general, in the question of Muslim attitudes toward violence. Key Features: Satisfies increasing interest in the issue of Muslim attitudes toward violence, highlighting the complexity of this topic and the diversity of Muslim attitudes toward violence. Offers an overview of the economy of violence under the various dynasties/governments that shaped the history of Islamic civilization. Incorporates innovative and novel approaches to violence as a feature of social and political organization. Contributions are written by well-known scholars in the field, providing up-to-date scholarship that spans languages (primary and secondary) and academic disciplines.